Analysis of the Role of Tourism Asset Redistribution in Promoting Local Economic Empowerment in the Bangsring Underwater Tourism Area, Banyuwangi - M. Aufa Oktavin Ramdani; Adil Siswanto (Danadyaksa: Post Modern Economy Journal, 2026)
This study analyzes the role of tourism asset redistribution in promoting local economic empowerment in the Bangsring Underwater tourism area, Banyuwangi. The development of community-based tourism in coastal areas has created various economic opportunities for local communities, particularly through the redistribution of tourism-related assets such as business access, employment opportunities, marine resource management, and local entrepreneurship. This research aims to examine how the redistribution of tourism assets contributes to improving community welfare and strengthening local economic resilience. The study employs a qualitative descriptive approach using interviews, observations, and documentation techniques involving local residents, tourism managers, and related stakeholders. The findings indicate that tourism asset redistribution has a significant role in increasing community income, encouraging the growth of micro and small enterprises, expanding employment opportunities, and enhancing community participation in tourism management. However, several challenges remain, including unequal access to resources, limited managerial capacity, and environmental sustainability issues. Therefore, collaborative governance and inclusive tourism management are essential to ensure sustainable local economic empowerment in the Bangsring Underwater tourism area.